Low-Voltage IGZO Field-Effect Ultraviolet Photodiode - Song, Shuang; Liang, Huili; Huo, Wenxing; Zhang, Guang; Zhang, Yonghui; Wang, Jiwei; Mei, Zengxia (Chinese physics letters, 2024)
In the era of Internet of Things (IoTs), an energy-efficient ultraviolet (UV) photodetector (PD) is highly desirable considering the massive usage scenarios such as environmental sterilization, fire alarm and corona discharge monitoring. So far, common self-powered UV PDs are mainly based on metal-semiconductor hetero-structures or p–n heterojunctions, where the limited intrinsic built-in electric field restricts further enhancement of the photoresponsivity. In this work, an extremely low-voltage field-effect UV PD is proposed using a gate-drain shorted amorphous IGZO (a-IGZO) thin film transistor (TFT) architecture. A combined investigation of the experimental measurements and technology computer-aided design (TCAD) simulations suggests that the reverse current ( I R ) of field-effect diode (FED) is highly related with the threshold voltage ( V th ) of the parental TFT, implying an enhancement-mode TFT is preferable to fabricate the field-effect UV PD with low dark current. Driven by a low bias of −0.1 V, decent UV response has been realized including large UV/visible ( R 300 / R 550 ) rejection ratio (1.9 × 10 3 ), low dark current (1.15 × 10 −12 A) as well as high photo-to-dark current ratio (PDCR, ∼ 10 3 ) and responsivity (1.89 A/W). This field-effect photodiode provides a new platform to construct UV PDs with well-balanced photoresponse performance at a low bias, which is attractive for designs of large-scale smart sensor networks with high energy efficiency.